Reduced-dimensional perovskite enabled by organic diamine for efficient photovoltaics - Niu, Tingting (2019)
Reduced-dimensional (RD) perovskite solar cells (PSCs) are emerging as highly attractive alternatives to three-dimensional (3D) PSCs due to their dramatically improved environmental stability and photostability. Diamine-based RD perovskites with a single organic amine interlayer possess orderly inorganic sheets and a smaller insulation area, indicating great potential in combining high efficiency and long-term stability. Here, we report an efficient and stable RD PSC based on 1,4-butanediamine (BDA). We found that the BDA-based RD perovskite exhibits improved crystallinity, reduced trap-state densities, and enhanced charge mobility compared to those of butylamine (BA)-based RD (BA-RD) perovskite. A high power conversion efficiency of 17.91% was achieved with negligible hysteresis. Moreover, the device showed improved stability compared to those of BA-RD and 3D films and devices. The findings may inspire new developments in introducing organic diamine for efficient and stable RD PSCs.